Bridging the gap: Do fast-reacting fossil technologies facilitate renewable energy diffusion?. (May 2018) - Verdolini, Elena; Vona, Francesco; Popp, David
Abstract: The diffusion of renewable energy in the power system implies high supply variability. Lacking economically viable storage options, renewable energy integration is possible thanks to the presence of modern mid-merit fossil-based technologies, which act as back-up capacity. This paper discusses the role of modern fossil-based power generation technologies in supporting renewable energy investments. We study the deployment of these two technologies conditional on all other drivers in 26 OECD countries between 1990 and 2013. We show that moving from the first to the third quartile of the distribution of modern fossil technologies is associated with an increase in yearly renewable energy investment of between 6 and 14 kW per thousand people, on average and ceteris paribus. This is a sizeable effect, considering that average yearly renewable capacity addition in our sample are around 12 kW per thousand people. These findings are robust to different econometric specifications, various definitions of modern fossil technologies and are stronger for wind, which is more intermittent and for which the mismatch between supply and demand is more marked. Our analysis points to the substantial indirect costs of renewable energy integration and highlights the complementarity of investments in different generation technologies for a successful decarbonization process. Highlights: We discuss how modern fossil power generation supports renewable energy investments. We show that higher gas-fired capacity is associated with more renewable investments. We highlight the substantial indirect costs of renewable energy integration.